SURVEI BIAYA INVESTASI AWAL PLTS ATAP DI INDONESIA TAHUN 2022 - Yudi Pramayasa, I Putu; Satya Kumara, I Nyoman; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 9 No 3 (2022): Jurnal SPEKTRUM, 2022)
The slow development of New and Renewable Energy such as solar energy in Indonesia are influenced by land acquisition and the high initial investment costs, but lately the cost of solar power plant development prices has been decreasing globally year by year. This research will review the development of PV mini-grid investment costs in Indonesia and this information can be used as a source of information for stakeholders to understand the development of PV mini-grid prices in 2022. The price of the solar power plant construction was obtained through a survey from the e-commerce website. From the survey, 55 data has been obtained related to the price of solar power plant rooftop construction in Indonesia with a capacity scale of 1 KWp to 10 KWp with price range from Rp. 14,000,000 to Rp. 207,000,000. The average initial investment cost for the construction of a PLTS Roof in Indonesia with a capacity of <2 KWp is Rp. 22,954,000, <3 KWp is Rp. 42.838.000, <4 KWp is Rp. 60,716,000, <5 KWp is Rp. 64,473,000, <6 KWp is Rp. 82,986,000, 6 KWp is Rp. 102,380,000, 7 KWp is Rp. 117,580,000, 8 KWp is Rp. 140,980,000, 9 KWp is Rp. 156.580.000, and 10 KWp is Rp. 151,820,000.